Implementasi Mekanisme Pengiriman Data Kesehatan Berbasis Protokol Bluetooth Low Energy antara Smartwatch dengan IoT Middleware - Reza Azzubair Wijonarko; Eko Sakti Pramukantoro; Fariz Andri Bakhtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The data sending mechanism between a resource-constrained sensor and an Internet-of-Things middleware (IoTM) must be considered to enable remote and periodical data recording. Such recording is paramount in the context of human heart monitoring. In a previous study, Bluetooth was used in a health-data sending mechanism from sensor to smartphone. However, the solution introduced new problem that is silo. Meanwhile, the Bluetooth Low Energy (BLE) protocol is more compatible to the resource-constrained sensor and has safe radiation levels. Also, the smartwatch is popular for recording human heart rate. Then, the silo can be averted by applying event-driven IoTM. Thus, this research proposes a health data-sending mechanism from smartwatch to IoTM utilizing BLE by implementing BLE gateway on the IoTM. The health data is the smartwatch user's heart rate measurement. The health data are uploaded to a cloud server via IoTM's internet gateway device (IGD) for analyzing. The research's result is a functional health data-sending mechanism that satisfies the sensor's resource-constrained characteristic. The health data has a maximum size of 17 byte. The optimal distance between the smartwatch and the IoTM is 10 meters, with a maximum end-to-end delay of 3.7 seconds and a minimum Packets Reception Ratio of 96%.